Eight common genetic variants associated with serum DHEAS levels suggest a key role in ageing mechanisms. - Guangju Zhai; Alexander Teumer; Lisette Stolk; John R B Perry; Liesbeth Vandenput; Andrea D Coviello; Annemarie Koster; Jordana T Bell; Shalender Bhasin; Joel Eriksson; Anna Eriksson; Florian Ernst; et al. (PLoS Genetics)
Dehydroepiandrosterone sulphate (DHEAS) is the most abundant circulating steroid secreted by adrenal glands--yet its function is unknown. Its serum concentration declines significantly with increasing age, which has led to speculation that a relative DHEAS deficiency may contribute to the development of common age-related diseases or diminished longevity. We conducted a meta-analysis of genome-wide association data with 14,846 individuals and identified eight independent common SNPs associated with serum DHEAS concentrations. Genes at or near the identified loci include ZKSCAN5 (rs11761528; p = 3.15 × 10(-36)), SULT2A1 (rs2637125; p =  2.61 × 10(-19)), ARPC1A (rs740160; p =  1.56 × 10(-16)), TRIM4 (rs17277546; p =  4.50 × 10(-11)), BMF (rs7181230; p = 5.44 × 10(-11)), HHEX (rs2497306; p =  4.64 × 10(-9)), BCL2L11 (rs6738028; p = 1.72 × 10(-8)), and CYP2C9 (rs2185570; p = 2.29 × 10(-8)). These genes are associated with type 2 diabetes, lymphoma, actin filament assembly, drug and xenobiotic metabolism, and zinc finger proteins. Several SNPs were associated with changes in gene expression levels, and the related genes are connected to biological pathways linking DHEAS with ageing. This study provides much needed insight into the function of DHEAS.